In a digitally connected world through Likes, Hashtags and Followers — Advancing surgical research through a social media: A narrative review - Sabah Uddin Saqib; Qamar Riaz; Russell Seth Martins; Amna Riaz; Hasnain Zafar (Journal of the Pakistan Medical Association, 2022)
In this era of modern information technology, the world is now digitally connected through various platforms on social media, which has also changed the way medical professionals work, communicate and learn. The use of social media in surgery is expanding, and it is now becoming an essential tool for surgical training, research and networking. Articles, journal clubs and surgical conferences are within reach of everyone regardless of geographical location worldwide. Electronic publications have now resoundingly replaced printed editions of journals. Collaborative research through social media platforms helps collect diverse data, enhancing the research's global generalisability. The current narrative review was planned to discuss the importance of social media in advancing surgical research and the use of different social media applications in the context of promoting and disseminating surgical research alongside its evolving ethical challenges. Continuous...